The link between financial education and financial literacy: A cross-national analysis. - Jerrim, John; López-Agudo, Luis Alejandro; Marcenaro-Gutiérrez, Óscar David (Taylor & Francis, 2022)
Financial literacy is a competence that extends to many aspects of everyday life. The Great Recession has recently highlighted its relevance and the importance of financial literacy training in the school curricula. The authors use PISA 2015 data to investigate the link between financial education and young people’s financial literacy across 15 countries using a student fixed-effects approach. Their results illustrate how financial education is still in its infancy within many countries and does not seem to improve young people’s ability to apply financial skills in real-world situations.
https://openpolicyfinder.jisc.ac.uk/id/publication/18978
Keywords: Educación financiera; Finanzas - Estudio y enseñanza; Educación - Modelos matemáticos; Financial education; Financial literacy; PISA2015; Student fixed-effects